Na tessitura dos processos de identidade dos Prounistas/Unisinos: a contribuição do programa de inclusão educacional e acadêmica - Silva, Aline Enriconi da (Universidade do Vale do Rio dos Sinos, 2014)
This paper focuses on investigating in the identity processes of prounista students at UNISINOS the contribution of the Academic and Educational Inclusion Program - AEIP. The program, based on the ignatian proposal, aims at academic excellence directed toward the promotion of justice, social inclusion, and the development of a sustainable society, through a reflective and committed process to its time. The AEIP offers full and partial scholarship and Additional Support to scholars, seeking to ensure access, attendance, as well as educational and academic success. The research, supported by a qualitative analysis, analyzes and discusses the identity processes from the background of five prounistas students of UNISINOS. A documental investigation was carried out, referring to MEC legislation, the National Education Plan (NEP), ASAV Educational Policy, and AEIP/UNISINOS database. In addressing the identity processes, the references used were: Jose Ivo Follmann, Stuart Hall, and Sygmunt Bauman; other references used were: Anthony Giddens, Jacques Delors, Immanuel Wallerstein, among others. This research aimed to examine how those subjects, often anonymous and invisible, are building their identity processes from their insertion in AEIP/UNISINOS.
Keywords: Processos de identidade; Programa de inclusão educacional e acadêmica; NEABI/UNISINOS; Identity processes; Academic and educational inclusion program; ACCNPQ::Ciências Humanas::Sociologia